When the Modifications Made to the Foggara Disturb the Environment - GHACHI, Nourad; REMINI, Boualem; HAMOUDI, Saaed (GeoScience Engineering, 2021)
This paper examines, for the first time, the consequences of modifications to the Foggara system on the environment. During our work and research missions carried out in the oases of Touat, Gourara and Tidikelt during the last 20 years (period 2000–2020), we have observed new practices operated by land owners on the Foggara, namely changes introduced in different parts of the Foggara with the aim of improving the flow of the Foggara. Two materials, PVC and Cement, were introduced in the oases of Touat, Gourara and Tidikelt. The earthen Souagui were replaced by PVC and PEHD pipes and the earthen Madjens were changed to cement Madjens. These modifications turned out to be dramatic for the aesthetics and hydraulics of the Foggara. Such interferences may cause the disappearance of this ancestral heritage, and will have negative repercussions on tourism in the region. Keywords: Cement modification; Environment; Foggara; Oasis; PVC pipe.